Civil Society and The Market Question: Dynamics of Rural Development and Popular Mobilization (Palgrave MacMilan, 2005)
Rather than focusing upon advanced countries, where civil society growth is seen as a post-market development, this volume, edited by K.B.Ghimire, explores developing countries, with case studies examining grassroots developments and experiences. The desirability, efficiency and effectiveness of market institutions as viewed by civil society organizations is addressed in this important collection, which moves the debate from acceptance or criticism of global markets to focus upon the case of rural development where local social relations and economic exchange remain more powerful and relevant than the operation of markets.